Calliterpenone, a natural plant growth promoter from a medicinal plant Callicarpa macrophylla, sustainably enhances the yield and productivity of crops - Pandey, Praveen; Pandey, Shiv Shanker; Awasthi, Ashutosh; Tripathi, Arpita; Singh, Hemendra Pratap; Singh, Anil Kumar; Tandon, Sudeep; Kalra, Alok (Frontiers in Plant Science, 2022)
The global population is rising at an alarming rate, which is threatening food and nutritional security. Although chemical fertilizers and pesticides are important for achieving food security, their excessive usage critically affects soil health and adds up residues in the food chain. There is an increasing interest in identifying eco-friendly farm inputs that can improve crop productivity through sustainable agricultural practices. One of the common approaches to reduce chemical inputs in agriculture is the use of plant growth regulators (PGRs). Here, we demonstrate the benefits of a natural and novel plant growth enhancer “calliterpenone,” isolated from Callicarpa macrophylla, a medicinal plant, for increasing crop productivity in six crops viz., rice, wheat, potato, tomato, chickpea, and onion. Results revealed that the application of calliterpenone (foliar spraying or seed soaking) enhanced the yield of rice (28.89%), onion (20.63%), potato (37.17%), tomato (28.36%), and chickpea (26.08%) at 0.001 mM and of wheat (27.23%) at 0.01 mM concentrations in comparison to control. This enhancement in yield was reflected through improvements in its growth attributes, viz., spike length, tillers plant-1, seeds spike-1, plant height, and biomass. Furthermore, the exogenous application of calliterpenone could increase the endogenous level of indole-3-acetic acid (IAA) in all tested crops and decrease the content of abscisic acid (ABA) in a few. Trials conducted at farmers' fields showed an overall ~12% increase in rice yield (mean of 11 farmers’ fields ranging from 3.48 to 19.63%) and ~10% increase in wheat yield (ranging from 3.91 to 17.51%). The 0.001 mM of calliterpenone was the best effective dose for most crops except wheat, where a concentration of 0.01 mM was found to be the most optimal. This study indicates that the calliterpenone is a natural plant growth promoter that can be used in boosting the yields of multiple crops and would be an important input component of organic farming.